Anti-Inflammatory Activity of Pleurotus ostreatus, a Culinary Medicinal Mushroom, in Wistar Rats. (5th March 2020) - Jayasuriya, W. J. A. Banukie N.; Handunnetti, Shiroma M.; Wanigatunge, Chandanie A.; Fernando, Gita H.; Abeytunga, D. Thusitha U.; Suresh, T. Sugandhika
Abstract : Context . Pleurotus ostreatus ( P.o ) is a culinary mushroom which is commonly called as "oyster mushroom" belonging to the Basidiomycetous fungi of the order Agaricales and family Pleurotaceae. Objectives . The present study investigates the anti-inflammatory potential of P.o and the underlying mechanisms of activity. Materials and Methods . Anti-inflammatory activity was evaluated using suspensions of freeze-dried and powdered (SFDP) P.o and acetone extract (AE) of P.o in normal and alloxan-induced diabetic rats using the carrageenan-induced rat paw oedema model. The mechanisms by which P.o is mediating the anti-inflammatory activity were studied using in vivo and in vitro assays. Results . At doses of 500–1000 mg/kg, the SFDP of P.o showed long-lasting activity at both early and late phases of carrageenan-induced rat paw oedema. The dose of 750 mg/kg showed the most potent inhibitory activity (92% inhibition) in healthy rats. The AE of P.o showed maximum inhibition of oedema of 87%. P.o exerted protective effects on the inflammatory pathologies in rats with diabetes. The possible mechanisms by which P.o mediates the anti-inflammatory activity were antihistamine activity (52.1%), inhibition of cell migration to the site of inflammation (45.4%), in vitro membrane stabilizing activity (52.6%), and inhibition of nitric oxide (NO) production (91.2%) (P < 0.05 ). Dose-dependent inhibition of NO production was seen with in vitro treatment of rat peritoneal cells with AE of P.o ( r = 0.95; P < 0.05 ). Discussion and Conclusion. The promising activity of culinary mushroom P.o against inflammation suggests its potential application as a functional food during inflammatory conditions.